Analisis Deiksis Cerpen dalam Buku Bahasa Indonesia Kelas VIII Kurikulum Merdeka - Nur Saidah; Ras Tuti Analiah; Ananda Putri Risang Ayu; Wiwik Fitriyani; Arif Setiawan; Asep Purwo Yudi Utomo; Dyah Prabaningrum (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research examines deixis in short stories in Buku Bahasa Indonesia Kelas XIII Kurikulum Merdeka, which aims to identify and describe deixis, which is divided into personal, place, time, discourse, and social deixis. The method used is a qualitative and pragmatic descriptive approach, with the data source being short stories in the Buku Bahasa Indonesia Kelas VIII Kurikulum Merdeka. The analytical method in this research is the agih method, which uses data in the form of fragments of words and phrases contained in the short story "Kotak Sulap paman Tom and Parki dan Alergi Telur". Data was collected using reading, note-taking, analysis, and classifying techniques based on type. Data analysis was carried out using the Agih method. This research obtained 10 person deixis, 33 time deixis, 13 place deixis, 121 discourse deixis, and 10 social deixis. It is known that discourse deixis is used more often in short stories, with the highest number among other deixis. The benefits of this analysis can be used as a reference regarding deixis and to find out the use of deixis in literary works in the form of short stories.